Euphonic Language Means in the Confessional and Official Document Written Monuments of the XIV–XV cent.: Alternation of у / в (Linguostylistic Studies, 2017)
The article explores the phenomenon of у / в alternation in the written monuments of the Ukrainian confessional and documentary writings of XIV-XV centuries. The author lays emphasis on the examples of linguistic parallelism in the documents, their consequentness in ancient manuscripts of various styles and their dissemination in the Ukrainian dialectal domains. The study has revealed numerous cases of the sounds alternation recorded in old writings, representing various kinds of the у / в /во / оув / оу во spelling: оу печаль – в Острозѣ – во истиноу – оув озера – оу  во Лвовѣ; оубогымъ – въбогымъ, вжитки – оужитки, всякій  – оусѧкии, оутороѥ – во вътрии же дн҃ь, вчити – оучать and many others. Yet, at the beginning of the XIV century, the у / в alternation was a well-established phenomenon, since both documentary writings and sacred texts from the northern and south-western regions of Ukraine reflect it regularly. Further research of the Old Ukrainian written monuments of different functional styles is needed to trace the formation of the main distinctive features of the Ukrainian national linguistic system.
Keywords: Ukrainian language; written monuments; confessional style; official-business style; variability; alternation